Characterisation of a long-term cell line (SHK-1) developed from the head kidney of Atlantic salmon (Salmo salarL.) - DANNEVIG, B.H.; BRUDESETH, B.E.; GJØEN, T.; RODE, M.; WERGELAND, H.I.; EVENSEN, Ø.; PRESS, C.McL (Fish & shellfish immunology, 1997)
A recently established cell line from Atlantic salmon head kidney, SHK-1, was characterised with respect to phenotypic and functional properties. The cell line was derived from a macrophage-enriched cell culture. Proliferating cells appeared after several weeks in culture, but did not resemble macrophages. The cells were flattened and elongated with a variable morphology. Subcultured cells had a more homogeneous morphology. No reactivity for alkaline phosphatase was observed in cytocentrifuge preparations of SHK-1 cells, while strong to moderate reactivity was detected for acid phosphatase, non-specific esterase, Mg2+-dependent adenosine triphosphatase and 5′ nucleotidase. The SHK-1 cells reacted with monoclonal antibodies (MAbs) directed against human cytokeratin and porcine vimentin. No reaction was observed after staining with MAbs against Atlantic salmon and rainbow trout serum immunoglobulins (Ig). The cells reacted strongly with MAbs directed against Atlantic salmon peripheral blood leucocytes but not with a MAb specific for Atlantic salmon polymorphonuclear leucocytes. The SHK-1 cells did not endocytose protein ligands which are recognised by the scavenger, mannose- and galactose-specific receptors. Specific uptake of transferrin or Atlantic salmon Ig could not be demonstrated. The SHK-1 cells did phagocytose the fish pathogenAeromonas salmonicidato some extent, but no bactericidal activity was observed over a period of 72h. Thus, from this profile of phenotypic and functional properties, it is concluded that the SHK-1 cell line is derived from leucocytes that have some of the properties of a macrophage.